Bench Testing and Modeling Analysis of Optimum Shifting Point of HMCVT - Yu Qian; Zhun Cheng; Zhixiong Lu (Complexity)
The unreasonable shift point will cause a large shift impact, which will affect the engine fuel economy and the service life of the wet clutch. To decrease shift impact on agricultural tractors with HMCVT (Hydromechanical Continuously Variable Transmission) and find the best working point, the following methods are proposed in this paper: firstly, conducting all-factor method and response surface method (RSM) to design and carry out bench test of shift impact; secondly, using the basic linear fitting, RSM, and stepwise regression analysis to establish comprehensive mathematical models and selecting models with high prediction accuracy; thirdly, putting forward the method of determining the weight of variance to match parameters of three quality evaluation indexes with inconsistent correlation; finally, establishing the total shift quality evaluation index and obtaining the optimal shift working point. It is found that oil filling pressure has a significant effect on speed drop, while the engine speed has a significance on the dynamic load and sliding friction. To make the transmission section of the best quality, the oil pressure at this time is 1 MPa and the engine speed is 1040 r/min. The results show that the proposed method can determine the optimal shift point and provide a reference for developing the control strategy.